2003
DOI: 10.1023/a:1025046723320
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Summary 5Disease symptoms and total soluble phenolics content have been analysed in four sunflower (Helianthus annuus L.) lines with different resistance levels (from highly susceptible to resistant) to head rot caused by Sclerotinia sclerotiorum (Lib.) de Bary. 10At the beginning of the flowering stage, capitula were inoculated by spraying with a water suspension of ascospores, and disease symptoms were evaluated from day 6 to day 14 after inoculation. The most susceptible genotypes showed all their ovarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The changes in TPC and individual phenolic content during the sunflower growth cycle reported in the present study can be linked with the physiological role of phenolic compounds in plants. In sunflower tissues, caffeoylquinic acids are considered to be precursors of coumarins (e.g., scopoletin, scopolin and ayapin) which, in turn, play a role in biotic and abiotic stress resistance [26,41,42]. Prats et al [42] reported that the total content of soluble phenolics in sunflower capitula was correlated with resistance to Sclerotinia sclerotiorum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in TPC and individual phenolic content during the sunflower growth cycle reported in the present study can be linked with the physiological role of phenolic compounds in plants. In sunflower tissues, caffeoylquinic acids are considered to be precursors of coumarins (e.g., scopoletin, scopolin and ayapin) which, in turn, play a role in biotic and abiotic stress resistance [26,41,42]. Prats et al [42] reported that the total content of soluble phenolics in sunflower capitula was correlated with resistance to Sclerotinia sclerotiorum.…”
Section: Resultsmentioning
confidence: 99%
“…In sunflower tissues, caffeoylquinic acids are considered to be precursors of coumarins (e.g., scopoletin, scopolin and ayapin) which, in turn, play a role in biotic and abiotic stress resistance [26,41,42]. Prats et al [42] reported that the total content of soluble phenolics in sunflower capitula was correlated with resistance to Sclerotinia sclerotiorum. In turn, Fernandez et al [25] selected caffeoylquinic acids as putative markers of drought stress in sunflower leaves.…”
Section: Resultsmentioning
confidence: 99%